Pengembangan Buku Siswa Bercirikan Realistic Mathematics Education (RME) untuk Meningkatkan Kemampuan Literasi Numerasi Siswa - Aini, Khafidhoh Nurul; Asmana, Arezqi Tunggal; Syafa’atin, Nur (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research purpose to develop a student book characterized by Realistic Mathematics Education (RME) in terms of validity, practicality, and effectiveness test results. The development of this student book uses the Plomp model, which is carried out in three phases, namely: (1) Preliminary research, (2) Prototyping phase, (3) Assessment phase. In the Preliminary research phase, it was found that numeracy literacy skills at SDN 2 Padenganploso were still low, and the teaching materials used did not include problems in daily life that were relevant to the environmental conditions around the students. In the Prototyping phase, student books are developed using steps that are in accordance with the principles and characteristics of RME. In the Assessment phase, based on the results of expert validation, an average score for all aspects was obtained of 3.86, which means that the RME student book can be said to be valid. From the results of observing the implementation of the student book, a score of 3.87 was obtained, which means that the practicality test by the observer met the Practical criteria. From working on numeracy literacy questions, 90% of students obtained a score above 65, and the overall N-Gain calculation results obtained an average score of 0.71 with a high interpretation. The results of observing student activities obtained an average of 3.8 in the active category, and the results of student responses were found to be 90% giving positive responses, which means that student books characterized by RME meet the Effective criteria